Ferroelectric-like organic–inorganic interfaces. Issue 44 (16th October 2020) - Yang, Linlin; Guo, Jianxin; Li, Jian; Yan, Jun; Ge, Kunpeng; Jiang, Jiayue; Li, Han; Flavel, Benjamin S.; Liu, Baoting; Chen, Jianhui
Abstract : Ferroelectricity is observed to occur at the interface between two non-ferroelectric materials, a polymer and silicon. Abstract : Since its discovery ferroelectricity has been an intriguing phenomenon in materials science and is usually observed in a single ferroelectric material. In this study, it is shown that ferroelectriciy can also occur at the interface between two non-ferroelectric materials, a polymer and silicon, and interfacial ferroelectric-like behavior is demonstrated. Sulfonic functional groups on the polymer establish electrochemically switchable dipoles, which are considered to be the origin of ferroelectric polarization and are observed in an atom-thick polar region at the interface. Above room temperature polarization hysteresis loops with long term stability, thermal stability, reliable switching reproducibility and long information retention directly on rigid and flexible silicon substrates are demonstrated. This exotic ferroelectric phenomenon extends polarization switching beyond singular materials and has the potential to advance the design of new ferroelectric devices.